2016
DOI: 10.1007/s11307-016-0994-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative [18F]FMISO PET Imaging Shows Reduction of Hypoxia Following Trastuzumab in a Murine Model of HER2+ Breast Cancer

Abstract: Purpose Evaluation of [18F]-FMISO-PET imaging as a metric for evaluating early response to trastuzumab therapy with histological validation in a murine model of HER2+ breast cancer. Procedures Mice with BT474, HER2+ tumors, were imaged with [18F]-FMISO-PET during trastuzumab therapy. Pimonidazole staining was used to confirm hypoxia from imaging. Results [18F]-FMISO-PET indicated significant decreases in hypoxia beginning on day 3 (P < 0.01) prior to changes in tumor size. These results were confirmed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…Evaluation of immune cell characterization and impact on tumor regression using the present study's treatment regimen is needed to further elucidate mechanisms contributing to enhanced tumor regression in the combination treatment group. Although no signi cant differences were shown in hypoxia or the vascular maturation index, previous studies using longitudinal imaging have indicated that trastuzumab can reduce hypoxia and increase vascular perfusion [17,29]. It is possible, by employing longitudinal imaging methods, windows of heightened oxygenation could be identi ed and that appropriately altered order of dosing could enhance treatment response in vivo.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Evaluation of immune cell characterization and impact on tumor regression using the present study's treatment regimen is needed to further elucidate mechanisms contributing to enhanced tumor regression in the combination treatment group. Although no signi cant differences were shown in hypoxia or the vascular maturation index, previous studies using longitudinal imaging have indicated that trastuzumab can reduce hypoxia and increase vascular perfusion [17,29]. It is possible, by employing longitudinal imaging methods, windows of heightened oxygenation could be identi ed and that appropriately altered order of dosing could enhance treatment response in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, breast tumors can become hypoxic due to the irregular and tortuous vasculature which increases radioresistance [12][13][14]. Previous results in HER2+ breast cancer have revealed that treatment with trastuzumab can increase tumor oxygenation in a preclinical mouse model through stabilization of tumor blood vessels [17]. Although there has been investigation into the potential ability of trastuzumab to radiosensitize breast cancer, data quantifying sensitization over time has been lacking, thereby reducing clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Trastuzumab, a monoclonal anti-HER2 antibody, is a targeted therapy used in the treatment of HER2+ breast cancer and has led to reduced recurrence of disease and dramatic improvements in patient survival [12] , [16] , [17] . In addition to its cytotoxic mechanisms, trastuzumab has been shown to alter tumor vasculature and oxygenation as a secondary mechanism of action [18] , [19] , [20] , [21] . Although trastuzumab has improved the treatment of locally advanced HER2+ breast cancer, only 30% of patients respond effectively to trastuzumab therapy in combination with other standard-of-care treatments [12] , [16] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…With the goal of achieving personalized treatment strategies, the well-known inter- and intra-tumor heterogeneity and the upcoming advanced imaging technologies have stimulated various researches on tumor characterization, treatment response assessment, and outcome prediction [ 1 10 , 12 14 , 16 18 ]. Consequently, dose painting strategies that aim to overcome treatment resistance by locally increasing the dose to the potentially more radio-resistant target sub-regions have been conceptually proposed and have been clinically introduced in selected studies for lung and head and neck cancer [ 11 , 15 , 19 , 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For hypoxia imaging, [ 18 F]fluoromisonidazole ([ 18 F]FMISO) has become a frequently used radiotracer. PET imaging with this tracer has proven to be useful in the assessment and prediction of the outcome of different types of cancer therapy [ 12 , 13 ]. Hypoxia is known to cause radiation treatment resistance and therefore new therapeutic strategies are targeting this crucial tumor feature.…”
Section: Introductionmentioning
confidence: 99%